Relationship between dietary cholesterol, egg consumption and lipid profile in apparently healthy adults according to age group - Oriondo Gates, Rosa Lorenza (2013)
Objectives: To determine the relationship between dietary cholesterol, egg consumption and lipid profile in apparently healthy adults according to age group. Design: Descriptive cross-association study. Setting: Biochemistry and Nutrition Research Center, Faculty of Medicine, Universidad Nacional Mayor de San Marcos. Participants: Apparently healthy adults. Interventions: In 50 apparently healthy adults dietary cholesterol consumption, egg and lipid profile were determined. Results: Thirteen participants consumed less than 3 eggs / week, 19 consumed from 3-4 eggs / week and 18 consumed more than 4 eggs / week. The 20-29 year-old group had an average intake of dietary cholesterol (358,9 ± 152,5 mg / dL) significantly higher (p <0,05) than the group 30-39 year-old (223 ± 82, 8 mg / dL). Total cholesterol (chol) of the three groups according to egg consumption was respectively 179,8 ± 52, 168,8 ± 44, and 164,3 ± 62 mg / dL; for HDL-chol 38,9 ± 15 , 28,0 ± 15, and 35,2 ± 14 mg / dL; for LDL-chol 118,1 ± 41, 112,5 ± 39, and 100,4 ± 47,9 mg / dL; for triglycerides 199, 2 ± 169, 152,8 ± 108, 124,2 ± 92 mg / dL. Conclusions: The consumption of dietary cholesterol and eggs in the sample was not related to the lipid profile.